(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Progressive collapse analysis of moment resisting steel frame is presented. Structural model and its analysis executed using STAAD PRO V8 for three different threat-independent column removal conditions by following the alternative load path method. Column removal is permitting to the General Service Administration (GSA-2003) guidelines for estimating progressive collapse potential. Results are shown for recreation in which a critical structural member is removed.